Learning and agency for sustainability transformations: building on Bandura's theory of human agency. Issue 1 (2nd January 2023) - Koskela, Iida-Maria; Paloniemi, Riikka
Abstract: How to secure a sustainable future is currently one of the key challenges across society. Bandura's theory of human agency provides important insights into this question by recognising the role of individual, proxy and collective agency in initiating action and change. In this article, we conceptualise sustainability agency and discuss psychological features and competencies that are relevant for supporting agency in sustainability education. Agency may manifest in different forms and contexts: countless actions in individual lives, communities, and local, national and global scenes can contribute to sustainability. This range of opportunities to be engaged in sustainability transformations can be better acknowledged in sustainability education in formal, non-formal and informal learning settings by broadening and clarifying the targets and indicators of successful sustainability education. Consequently, sustainability education and related participation in advancing sustainability can become more inclusive and meaningful for actors with diverse backgrounds.